Helicobacter pylori Oncogenicity: Mechanism, Prevention, and Risk Factors - Muzaheed (The Scientific World Journal)
Helicobacter pylori (H. pylori) is the most common cause of gastric ulcer; however, its association with gastric cancer has been proved through a variety of studies. Importantly, H. pylori infection affects around half of the world’s population leading to a variety of gastric problems and is mostly present in asymptomatic form. Although about 20% of people infected with H. pylori develop preneoplastic gastric lesions in later stages of their life, around 2% of infected individuals develop gastric cancer. Nevertheless, the outcome of H. pylori infection is determined by complex interaction between the host genetics, its environment, and virulence factors of infecting strain. There are several biomarkers/traits of H. pylori that have been linked with the onset of cancer. Among these, presence of certain major virulence factors including cytotoxin-associated gene A (CagA), vacuolating cytotoxin (VacA), and outer inflammatory protein A (OipA) plays a significant role in triggering gastric cancer. These factors of H. pylori make it a potent carcinogen. Therefore, eradication of H. pylori infection has shown positive effects on decreasing the risk of gastric cancer, but this has become a challenge due to the development of antibiotic resistance in H. pylori against the antibiotics of choice. Thus, the unmet need is to develop new and effective treatments for H. pylori infection, considering the antimicrobial resistance in different regions of the world. This review discusses the properties of H. pylori associated with increased risk of gastric cancer, antibiotic resistance pattern, and the possible role of eradication of H. pylori in preventing gastric cancer.